Loss of DMRT1 gene in a Mos 45,XY,-9[8]/46,XY,r(9)[29]/47,XY,+idic r(9)× 2[1]/46,XY,idic r(9)[1]/46,XY[1] female presenting with short stature - Bagas A. Marsudi; Hannie Kartapradja; Chrysantine Paramayuda; Jose R. L. Batubara; Alida R. Harahap; Nanis S. Marzuki (Molecular Cytogenetics, 2018)
Abstract Background A 46,XY sex reversal syndrome is characterized by discordant genetic and phenotypic sex, leading to normal external female genitalia, undeveloped gonads and presence of Müllerian structures in an otherwise 46,XY individual. Chromosome 9pter aberrations, such as ring chromosome have been reported to cause 46,XY disorders of sex development (DSD), due to involvement of DMRT1 gene located at the 9p24.3 region. Case presentation This study presents a unique case of a 12-year-old female with mos 46,XY, (r)9[31]/45,XY,-9[9] karyotype, presenting with intellectual disability and short stature, mimicking Turner syndrome. Re-karyotyping was performed using standard GTL-banding technique. Further cytogenetic study using standard metaphase fluorescent in situ hybridization (FISH) technique was applied to cultured lymphocytes from peripheral blood, hybridized using green control probe specific to 9q21 loci, and red DMRT1 probe specific to 9p24.3 loci. Cytogenetics and FISH analysis revealed mos 45,XY,-9[8]/46,XY,r(9)[29]/47,XY,+idic r(9)× 2[1]/46,XY,idic r(9)[1]/46,XY[1] and haploinsufficiency of DMRT1 gene in most cells. CGH array revealed a deletion around 1.25 Mb at 9p24.3 loci [arr 9p24.3(204,193-1,457,665)× 1] and three duplications around 13 Mb [9p24.3p22.3(1,477,660-14,506,754)× 3] near the breakage point that formed the ring chromosome 9. Conclusions The clinical presentation of the subject that mimics Turner syndrome highlights the importance of cytogenetic analysis to detect the possibility of ring chromosome 9. Sex reversal due to haploinsufficiency of DMRT1 gene in ring chromosome 9 structures is exceedingly rare with only a handful of cases ever reported. This finding further highlights the importance of DMRT1 gene in sex determination and differentiation in males. More research is required to pinpoint the exact mechanism that underlies sex reversal caused by DMRT1 haploinsufficiency.